Teacher’s Roles in Implementing Cooperative Learning in Teaching English to Senior High School Students - Olviani Cn. Tarinje (Sintuwu Maroso Journal of English Teaching, 2018)
This research aims to determine roles of teacher in implementing cooperative learning in teaching English. The research takes location at SMAN 3 Poso. This research is qualitative in nature, where the qualitative data are described descriptively. The subject is an English teacher at SMAN 3 Poso, where the data areobtained through observation and in-depth interview. The roles of English teacher at SMAN 3 Poso in implementing Cooperative Learning are described furthermore inthis article.Keywords: roles of teacher, Cooperative Learning